A Unified View on Nanoscale Packing, Connectivity, and Conductivity of CNT Networks. (4th February 2019) - Gnanasekaran, Karthikeyan; Grimaldi, Claudio; de With, Gijsbertus; Friedrich, Heiner
Abstract: The design of functional structures from primary building blocks requires a thorough understanding of how size, shape, and particle–particle interactions steer the assembly process. Specifically, for electrically conductive networks build from carbon nanotubes (CNTs) combining macroscopic characterization and simulations shows that the achievable conductivity is mainly governed by CNT aspect ratio, length dispersity and attractive interactions. However, a direct link between the actual 3D network topology that leads to the observed electrical conductivity has not been established yet due to a lack in nanoscale experimental approaches. Here it is shown experimentally for randomly packed (jammed) CNT networks that the CNT aspect ratio determines, as theoretically predicted, the contact number per CNT which in turn scales linearly with the resulting electrical conductivity of the CNT network. Furthermore, nanoscale packing density, contact areas, contact distribution in random and nonrandom configurations, and least resistance pathways are quantified. The results illustrate how complex nanoscale networks can be imaged and quantified in 3D to understand and model their functional properties in a bottom‐up fashion. Abstract : Carbon nanotube networks are imaged quantitatively in 3D to experimentally assess the effects of nanoscale packing density and contact distribution in random and nonrandom configurations. This allows for the establishment of a direct link between network topology and its electrical properties as a function of CNT aspect ratio and length polydispersity in a bottom‐up fashion.